(untitled) (World Bulletin of Social Sciences, 2023)
The article provides information about the development of the primary higher education institution in Karakalpakstan and the scientific and pedagogical staff working in it. Difficulties in the opening of the Karakalpak State University, the services of the government leaders, selfless compatriots are shown in terms of historical data